Pendapatan dan Daya Saing Ubi Kayu di Kabupaten Lampung Tengah (Forum Agribisnis, 2026)
The cassava sector in Lampung Province, particularly in Central Lampung Regency as the main production center, still faces various structural challenges. In 2023, cassava production reached 7.2 million tons with an average productivity of 27.5 tons per hectare, which is still below its optimal potential. Therefore, it is important to analyze the income level and competitiveness of cassava farming in Central Lampung Regency. The results indicate that the total production cost reached IDR 28,850,868.19 per hectare, while the revenue amounted to IDR 14,323,071.11, resulting in an R/C ratio of 0.496, which implies that cassava farming is not yet financially efficient. The Private Cost Ratio (PCR) values of 0.0906 in Terbanggi Besar and 0.1401 in Seputih Mataram show that cassava farming remains financially efficient in the use of domestic resources. Meanwhile, the Domestic Resource Cost Ratio (DCR) values of 0.0486 and 0.0944 indicate that cassava has a relatively strong comparative advantage in both regions. However, the Nominal Protection Coefficient on Output (NPCO) values below suggest that the output prices received by farmers are lower than the social prices. Therefore, government policies should focus on strengthening price protection at the farm level through the establishment of reference prices and the enhancement of partnerships with processing industries.